BENTUK SAPAAN DALAM BAHASA MELAYU DIALEK SATUN, THAILAND SELATAN - Sumaiyah Menjamin (MABASAN, 2017)
This study aims at describing the forms of addressing in Satun Dialect of Malay Language. This research is a descriptive field study of the terms of address in Satun dialect of Malay language in Southern Provinces of Thailand. The collected data are the forms of address used by community using Satun dialect of Malay language. The data were obtained from the interviews, literature study, etc., related to the terms of address in Satun dialect of Malay language. Data were collected by using Observational method or simak libat cakap method and interview. The data were analyzed by using referential identity method and contextual method. The findings are first, the terms of address obtained from the analysis can be categorized into three categorizations such as a) 23 monomorphemic forms, b) 29 polymorphemic forms, c) 4 phrase’ forms.The forms are changeable due to social factors. It is recommended that the addressing forms are used in daily life. It is also recommended to the upcoming research in the BMDSTS topic to improve and to investigate the research deeper.